2001
DOI: 10.1073/pnas.161274798
|View full text |Cite
|
Sign up to set email alerts
|

Acridine and phenothiazine derivatives as pharmacotherapeutics for prion disease

Abstract: Prion diseases in humans and animals are invariably fatal. Prions are composed of a disease-causing isoform (PrP Sc ) of the normal host prion protein (PrP C ) and replicate by stimulating the conversion of PrP C into nascent PrP Sc . We report here that tricyclic derivatives of acridine and phenothiazine exhibit half-maximal inhibition of PrP Sc formation at effective concentrations (EC50) between 0.3 M and 3 M in cultured cells chronically infected with prions. The EC 50 for chlorpromazine was 3 M, whereas q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
408
1
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 601 publications
(437 citation statements)
references
References 42 publications
(53 reference statements)
16
408
1
4
Order By: Relevance
“…One of the most commonly used cell line for in vitro prion studies is the mouse neuroblastoma cell line N2a which is readily susceptible to mouse adapted sheep scrapie prion strains. In fact, these cells can become chronically infected with the prion agent and have served as an in vitro model for testing potential therapeutic approaches against prion diseases [21,39]. Several recent reports demonstrated that non-neuronal cells can also support TSE infection.…”
Section: Page | 24mentioning
confidence: 99%
“…One of the most commonly used cell line for in vitro prion studies is the mouse neuroblastoma cell line N2a which is readily susceptible to mouse adapted sheep scrapie prion strains. In fact, these cells can become chronically infected with the prion agent and have served as an in vitro model for testing potential therapeutic approaches against prion diseases [21,39]. Several recent reports demonstrated that non-neuronal cells can also support TSE infection.…”
Section: Page | 24mentioning
confidence: 99%
“…The solution was cooled to °C, treated with Et 2 O (500 ml), and extracted with HCl (1M aq., 2×300 ml). The combined aqueous layers were washed with Et 2 O (200 ml), cooled to 0 °C , treated directly with solid NaOH until the mixture was visibly heterogeneous, and then extracted with EtOAc (3×200 ml), dried over Na 2 SO 4 , and concentrated in vacuo to yield the desired secondary amines (15) in high purity (50-71% yield).…”
Section: General Procedures For Amidation/reduction To Generate the Sementioning
confidence: 99%
“…Thus, a cluster of aromatic residues is formed in the peptide, which is solvent-exposed to a large part even in the structure of PrP. In addition to its importance for the stability of helix 1 itself and for the attachment of helix 1 to helices 2 and 3, this cluster of aromatic residues may play an important role for the binding of potential therapeutic drugs such as quinacrine (49). 2 Our data underline the importance of interleaved placement of i,iϩ4 electrostatic and aromatic interactions for the formation of stable helices.…”
Section: [De]-x-x-a-[rk]-x-x-[rk]-[de] Modeling the D147a Mutation Anmentioning
confidence: 99%